The incremental value of interatrial septum motion in predicting thrombus or spontaneous echo contrast in patients with non-valvular atrial fibrillation: an observational study on transesophageal echocardiography - Zeng, Decai; Chang, Shuai; Zhang, Xiaofeng; Zhong, Yanfeng; Yongzhi, Cai; Huang, Tongtong; Wu, Ji (Frontiers in Cardiovascular Medicine, 2024)
Background: The thickness and motion of the Interatrial Septum (IAS) possibly serves as indicators of both structural and functional remodeling of left atrium. This study aims to use transesophageal echocardiography (TEE) to assess IAS motion in non-valvular atrial fibrillation (NVAF) and investigate its correlation with the risk of spontaneous echo contrast (SEC) and thrombus (TH). Methods: We conducted a cross-sectional study on 318 patients with NVAF who underwent transthoracic echocardiography and TEE. IAS motion was defined as the maximum displacement of IAS observed throughout the cardiac cycles using M-mode TEE. Results: The prevalence of SEC/TH was 39.9% (127/318) in the overall group. In paroxysmal atrial fibrillation (PAF), the prevalence rate of SEC/TH was 25.3% (47/186), compared to 60.6% (80/132) in persistent atrial fibrillation (PeAF). Multivariable analyses showed that LA volume index (LAVI), mean E/e', S/D ratio, IAS motion and CHA2DS2-VASc scores were significantly associated with SEC/TH. Patients with lower IAS motion showed a higher prevalence of SEC/TH compared to those with higher IAS motion (71.3% vs. 11.6%; P<0.001). The IAS motion under sinus rhythm could better predict risk of SEC/TH, while the predictive efficacy under AF rhythm was slightly attenuated but still had a high AUC value (0.779). A significant positive correlation was observed between the IAS motion and the LAA filling velocity (PAF r = 0.47; P < 0.001 and PeAF r = 0.38; P < 0.001, respectively), LAA emptying velocity (PAF r = 0.55; P < 0.001 and PeAF r = 0.47; P < 0.001, respectively) and LAVI (PAF r = 0.59; P < 0.001 and PeAF r = 0.44; P < 0.001, respectively). The integration of the IAS motion to the CHA2DS2-VASc, LAVI and mean E/e' provided important incremental predictive value of SEC/TH (AUC = 0.859 vs. 0.826, P = 0.02). Conclusion: IAS motion measured by TEE correlates well with LAA flow velocity and LA size and is independently associated with SEC/TH in NVAF. Additionally, lower IAS motion is associated with a higher prevalence of SEC/TH. Furthermore, the integration of IAS motion to CHA2DS2-VASc, LAVI and mean E/e' can provide additional value for the prediction of SEC/TH.